Grupos de apoyo y depresión de los Jubilados del Instituto Ecuatoriano de Seguridad Social Riobamba, período octubre 2015 – marzo 2016. - Ruiz Naranjo, María Daniela (2016)
The present study was conducted in the Ecuadorian Institute of Social Security, located in Riobamba, term October 2015- March 2016, 80 retired people were considered in this study by the application of inclusive criteria that determined that 40 people suffer form depression. The purpose of the Project is to describe the influence of supporting groups in depressive retired people, the investigation utilized the scientific method, with a quantitative and quasi-experimental design, it was a transversal and a field research with a descriptive level. The techniques and instruments applied for data collection go as follow: A survey to value the perception of the supporting group of the retired people, a survey that indicates that 91% of these people consider that the supporting group contributes in a positive way in the decrease of symptoms that cause depression due to this group offers: Support, a warm environment, assistance with problematic situations to improve their social relationships to face retirement and reduce the feeling of feelings of worthlessness, being able to share their concerns, while summoned and directed the group by a professional (social worker), as regards the test Yesavage 65% of retirees have severe depression, while 35% have moderate depression, then these results were presented in tables and graphs to make conclusions and recommendations. After the analysis and interpretation of the results obtained, a therapeutic proposal to change the levels of depression retirees from the supporting group in the Ecuadorian Institute of Social Security, located in Riobamba obtaining important results that have helped reduce the depressed population.